On the optimization of approximate integration by Monte Carlo methods - Babenko, V. F. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We solve the problem of optimization of monte Carlo methods for approximate integration over an arbitrary absolutely continuous measure. We propose a convenient model of Monte Carlo methods which uses the notion of transition probability.